CONFLICT MANAGEMENT OF HALAL TOURISM DEVELOPMENT BASED ON LOCAL WISDOM FROM REGIONAL ECONOMIC EMPOWERMENT PERPECTIVE IN LAKE TOBA, NORTH SUMATERA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the problems of developing halal tourism based on local wisdom from theperspective of economic empowerment of local communities, especially in relation to preventingrejection from the community. Data were collected through qualitative methods with triangulationtechniques of observation, interviews, FGD and documentation. The data obtained is then analyzedaccording to its actual conditions, and then each element of the actual condition is combined to produceconclusions. The results showed that the plan to determine halal tourism, which is set by the government,is expected to be able to be responded to by the local community; Local wisdom of the local communityin responding to plans to determine halal tourism in improving economic living standards, can help theeconomy and tourism development without eliminating existing local wisdom; The results achieved bythe community regarding regional economic empowerment in the development of halal tourism, the NorthSumatra Provincial Government and related agencies collaborated with each other and providedsocialization with the local community. This tourism development is recommended to be continued.